Analysis Flexibility and Arm Muscle Strength on Badminton Smash Stroke Ability Avanti Makassar Club - Akhmad, Noor; Hasanuddin, M Imran; Awaluddin (Sportify Journal, 2022)
Effective badminton smash performance requires the integration of physical capacity, movement control, racket coordination, and the ability to generate a fast and accurate attacking stroke. This study examined the contribution of wrist flexibility and arm muscle strength to smash performance among players of Avanti Badminton Club Makassar. A quantitative descriptive-correlational design with a regression approach was used. The sample consisted of 40 badminton players, with complete valid data for all research variables. Wrist flexibility was measured using a flexiometer, arm muscle strength was measured using a 30-second push-up test, and smash performance was assessed using a badminton smash skill test. Data were analyzed using descriptive statistics, the Kolmogorov-Smirnov normality test, Pearson correlation, simple regression, and multiple regression. The results showed that wrist flexibility contributed significantly to smash performance, R = 0.802, R² = 0.643, p < 0.001. Arm muscle strength also showed a significant contribution, R = 0.815, R² = 0.665, p < 0.001. Simultaneously, both predictors explained 74.3% of the variance in smash performance, R = 0.862, R² = 0.743, F = 53.600, p < 0.001. These findings indicate that badminton smash performance is supported by the interaction between wrist mobility and upper-limb strength. Training programs should therefore combine arm-strength development, wrist-flexibility exercises, and smash-specific coordination drills.